An Analisa pertanyaan mahasiswa bahasa Inggris sebagai bahasa asing di kelas penelitian pembelajaran bahasa Inggris di universitas PGRI Ronggolawe Tuban - Panggabean, Christina Innocenti Tumiar; Asariski, Aisah (Universitas Nusantara PGRI Kediri, 2021)
This research was conducted to analyze the questions used by EFL students in Research on ELT ( English Language Teaching ) Class at University of PGRI Ronggolawe Tuban. This research was conducted to know the types of questions applied by the students, the most dominant questions used based on the cognitive domains of Bloom’s taxonomy, and the students’ responses towards the questions. Descriptive qualitative research design was applied in the research. The subject of the study were the sixth semester students who took Research on ELT course. To collect the data, observation using Telegram application and interview were applied. The data were analyzed qualitatively to determine the cognitive level of each question according to revised Bloom’s taxonomy. The result of the data analysis showed that the students used empirical questions as the type of questions. The dominant question used based on the cognitive domains of Bloom’s taxonomy was Analyzing level or C4 which appeared 48%. It showed that HOTS questions were the most used at the classroom with the total 64%, while the LOTS questions only got 36%. The students claimed that they felt interested and glad to answer the questions. It can be concluded that the students of Research on ELT class had shown that they had ability to think critically.